DHEA metabolites activate estrogen receptors alpha and beta - Michael Miller, Kristy K. (2012)
Dehydroepiandrosterone (DHEA) levels were reported to associate with increased breast cancer risk in postmenopausal women, but some carcinogen-induced rat mammary tumor studies question this claim. The purpose of this study was to determine how DHEA and its metabolites affect estrogen receptors α or β (ERα or ERβ) -regulated gene transcription and cell proliferation. In transiently transfected HEK-293 cells, androstenediol, DHEA, and DHEA-S activated ERα. In ERβ transfected HepG2 cells, androstenedione, DHEA, androstenediol, and 7-oxo DHEA stimulated reporter activity. ER antagonists ICI 182,780 (fulvestrant) and 4-hydroxytamoxifen, general P450 inhibitor miconazole, and aromatase inhibitor exemestane inhibited activation by DHEA or metabolites in transfected cells. ERβ-selective antagonist R,R-THC (R,R-cis-diethyl tetrahydrochrysene) inhibited DHEA and DHEA metabolite transcriptional activity in ERβ-transfected cells. Expression of endogenous estrogen-regulated genes: pS2, progesterone receptor, cathepsin D1, and nuclear respiratory factor-1 was increased by DHEA and its metabolites in an ER-subtype, gene, and cell-specific manner. DHEA metabolites, but not DHEA, competed with 17β-estradiol for ERα and ERβ binding and stimulated MCF-7 cell proliferation, demonstrating that DHEA metabolites interact directly with ERα and ERβ in vitro, modulating estrogen target genes in vivo.